Antimicrobial Resistance: What Should Dentists be Doing? - Montero-Aguilar DDS MSc, Mauricio (2016)
The purpose of this article is to increase awareness among the dental professionals about the importance of an adequate antibiotic stewardship in the dental setting, in light of the increasing threat that antimicrobial resistance represents to humanity. Updated guidelines for the prescription of antibiotic drugs must be followed by the dentist and patient education for the intake of these drugs are mandatory as part of a global strategy aimed to reduce the burden of disease and death caused by antimicrobial resistant microorganisms.